OTOMATISASI PENYIRAMAN TANAMAN DENGAN METODE SAW MENGGUNAKAN ARDUINO BERBASIS WEB - Nugroho, Atmoko; Daru, April Firman; Cahyono, Agus Edy (Jurnal Pengembangan Rekayasa dan Teknologi, 2017)
Plants need water to grow and develop. Planting crops in the home environment can provide many benefits, including ensuring the availability of oxygen in the family, as a natural cooling of the house, and as a storage groundwater if the plants get watering and routine maintenance, the benefits derived from plants will be perceived by the family. Using clean water to water the plants every day is a wasteful behavior of water, because water is used for everyday purposes. In addition, the dense activities result in the existing plants at home tend to be lazy to water the plants. Well-groomed plants can provide adequate oxygen for the family.Many ways can be done to solve problems, using soil moisture sensors and temperature sensors to monitor the state of the plant at home, to determine the time of watering using decision support system with the method of SAW (Simple Additive Weighting) to determine the time of watering based on the results of the sensor readings on plants. The existence of this system can be saving water used for watering plants, and plants in the house fulfilled water needs, the benefits of plants can be felt.
Keywords: Plant; Arduino Nano; SAW (Simple Additive Weighting)